Code:
|(a+b-c) (-c+a-b) (a+b+c) |
| (a-c) (c-a) (b-a) | = (a+b-c)(-c+a-b)(a-c)
| (a-b) (a-c) (a+b) |
using properties of determinants without expanding the determinant
I tried a lot of ways like with following steps C(3) -> C(3) + C(2) , R(1) -> R(1) + R(2) ,
R(1) -> R(1) + R(2) - R(3).....but i could get nothing...its not my homework sum....i am just a 6th grade maths enthusiast.....i saw this sum somewhere.....i tried to solve this but couldnt get.......can anyone help me up to solve this......or atleast guide me.......where C(1) means column 1 and R(1) means Row 1 and similar things to that